The Prophetic Year and its Educational Role in Building Islamic Personality and its Impact on Educational Institutions / A Fundamental Study - Abdullah, Dr. Paysharew Hamah Ali Abdullah (Sulaimani Journal for Humanities, 2026)
The Arabs before Islam lived an unjust and dark life, raiding one another, considering each other's wealth as permissible to take, killing their daughters out of fear of shame, and consuming each other's wealth unjustly—sometimes through excessive usury, sometimes through denial, and sometimes through usurpation. Despite this, they possessed the natural nobility of human nature and the noble morals that Allah had instilled in people by their very creation. If this indicates anything, it demonstrates their personal characteristics that crystallized as a result of the injustice they experienced in their era and the complex educational .traits they inherited from their ancestors Then Islam came and guided people to the true religion by the grace of Allah. The first challenge the Prophet faced after establishing the oneness of Allah in the hearts of his companions was to refine the Muslim personality and replace it with characteristics that Allah loves—those very qualities upon which He had created them by nature. Therefore, the pure Prophetic tradition (Sunnah) became rich with all educational methods that would refine the companions' personalities to suit the great religion of Islam. They absorbed these teachings, which then flowed from them to their students and children, passing them down generation after generation until Islam dominated the inhabited world and became the aspiration of everyone .with a sound natural disposition What the Islamic nation suffers from today—weakness, decay, and frailty—is nothing but the result of its departure from the noble Prophetic values. This study is but a drop in the vast ocean of the great Sunnah, intended to demonstrate to both near and far that his biography, guidance, and actions are the effective remedy for the chronic illness that afflicts the nation today.